System based on abstract prototyping and motion capture to support car interior design. Issue 2 (3rd March 2016) - Caruso, Giandomenico; Camere, Serena; Bordegoni, Monica
Abstract: The paper describes a system to supply meaningful insights to designers during the concept generation of new car interiors. The aim of the system is to capture the movements of car passenger's and making these acquisitions directly available as a generative input. The system has been developed by integrating the Abstract Prototyping technique with Motion Capture technology. In addition, a systematic procedure allows the treatment of the collected data to obtain a graphical representation, which can be easily used with standard NURBS-based modeling software. The effectiveness of the system has been evaluated through a testing session conducted with subjects. The outcomes of the testing sessions have highlighted benefits and limitations of the implemented system. GRAPHICAL ABSTRACT: